2018
DOI: 10.1177/0898264318781131
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Cognitive Impairment Among U.S. Veterans With a History of MDD or PTSD: A Retrospective Cohort Study Based on Sex and Race

Abstract: MDD and PTSD act as significant risk factors for dementia and other forms of cognitive impairment, and Black veterans, given a history of MDD, may be at an increased risk. An important endeavor for future research is to examine how this risk may vary across dementia subtypes and related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Our findings were consistent with those from a study of non-FDNY WTC responders, which reported that WTC exposure and PTSD symptoms were associated with worse performance on an objective cognitive measure [ 7 ]. They also accord with a large body of research showing PTSD symptoms and depressive symptoms to be risk factors for cognitive dysfunction, both in studies of veterans [ 8 , 9 , 10 ] and in general populations [ 11 , 12 , 13 ]. PTSD has been linked to reduced cognitive function even in studies of non-veteran trauma survivors in which trauma-exposed comparison groups without PTSD were used, such as natural disaster survivors or war victims [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our findings were consistent with those from a study of non-FDNY WTC responders, which reported that WTC exposure and PTSD symptoms were associated with worse performance on an objective cognitive measure [ 7 ]. They also accord with a large body of research showing PTSD symptoms and depressive symptoms to be risk factors for cognitive dysfunction, both in studies of veterans [ 8 , 9 , 10 ] and in general populations [ 11 , 12 , 13 ]. PTSD has been linked to reduced cognitive function even in studies of non-veteran trauma survivors in which trauma-exposed comparison groups without PTSD were used, such as natural disaster survivors or war victims [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 78%
“…Our results demonstrate that increased subjective cognitive concerns in the most highly WTC-exposed group vs. the lesser exposed group can be attributed to elevated levels of PTSD and depression, which are well-established risk factors for cognitive dysfunction [ 8 , 9 , 10 , 11 , 12 , 13 , 41 , 43 , 44 ]. In other words, mental health outcomes associated with greater WTC exposure, rather than WTC exposure alone, increase workers’ risk for subjective cognitive concerns.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Studies have reported racial disparities in self-reported health and prevalence of chronic disease among Veterans [17][18][19][20]. However, only a limited number of studies have investigated racial disparity of AD/ADRD in US Veterans [21,22]. The objective of our study was to determine the incidence of AD/ADRD among a national sample of African American and white Veterans, and to examine predictors of AD/ADRD overall as well as separately within these two populations.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies of PTSD and cognitive function were carried out in populations of military veterans (16,34,35); however, a connection between PTSD and cognitive impairment has also been observed in studies of individuals exposed to other types of trauma (12,13,36), as well as in one study involving a general population (14). In the previously noted cohort of non-FDNY WTC responders, PTSD symptoms were associated with an increased risk of cognitive impairment (15).…”
Section: Discussionmentioning
confidence: 95%